¨Comportamiento agronómico de cultivares de arroz (Oryza Sativa L.) a la Aplicación de fertilización nitro-fosforada, foliar y edáfica, en la zona de Babahoyo¨. - Castro Rodríguez, Adrián Arturo (2019)
IX. SUMMARY This research work was carried out on the grounds of the community "Carolina 2" of the Cooperativa 9 de Octubre, located at km 9.5 of the Babahoyo - Baba road of the Province of Los Ríos. The proposed objectives were: To determine the agronomic behavior of rice cultivars to the application of nitro-phosphorous, foliar and edaphic fertilization, in the Babahoyo area; evaluate the agronomic behavior of rice to nitro-phosphorus fertilizer applications; identify the most influential treatment on crop yield and perform an economic analysis in relation to the benefit / cost. The INIAP 16 and INIAP 1480 varieties were used as the sowing material. The treatments were composed of different levels of nitro-phosphorus fertilization (N 180, 142, 92, P 46, 43, 0) and Maxbio 0,5- 1.0 L / ha. The experimental design of subdivided plots with twelve treatments and three repetitions was applied. The comparison of the means was made with the Tukey test 5% probability. The data evaluated were plant height, number of tillers per plant, days to flowering, number of panicles per plant, length of panicles, weight of 1000 grains, yield and economic analysis. From the results obtained, it is detailed that the application of different levels of fertilization influenced the development process of the rice varieties. The interaction of the variety 1480 with the program of 184-86 Kg / ha N-P and 1.0 L / ha of Maxbio had better grain yield. All the agronomic variables were influences `by the application of the treatments in both varieties tested. The INIAP 16 variety reached higher yield, the employment of 184 kg / ha N + 46 kg / ha P (7500.42 kg / ha) had the highest production, while Maxbio 1.0 L / ha with 6710.83 kg / ha I generate more performance. The economic relationship found in the variety INIAP 1480 with the program 184 kg / ha N + 46 kg / ha P + Maxbio 0.5 L / ha (7949.0 kg / ha) the greatest economic benefit with 1205.43 dollars and a benefit-cost ratio of 1.97. Key Words: Production, fertilization, rice, foliar.